Determination of Parameter Sensitivity Maps of Surface Nonlinear and Focussed Geoelectric Arrays - Szalai, S.; Szarka, L.; Baracza, M. K.; Szucs, P. (Current Advances in Geography, Environment and Earth Sciences Vol. 4, 2022)
The aim of the study is to present parameter sensitivity maps of nonlinear and focussed electrode arrays. Understanding parameter sensitivity maps is fundamental to understand geoelectric arrays. These maps are presented as anomalies due to electric dipoles forming on opposing surfaces of an elementary cube within the subsurface at three different depths, and not only the total effect of the dipole, but also the effect of its components are shown. Parameter sensitivity maps of non-linear arrays, compared to those of linear arrays, have in general (1) more equal sensitivity values in x and y directions, (2) more chances for antisymmetry axes, (3) smoother lateral distribution of sensitivity values. In geoelectric prospecting, we advocate using parameter sensitivity maps in a systematic way, both in terms of planning and interpreting field results.